Possession Syndrome at High Altitude (4575 m/15000 ft) - Khan, ID; Sahni, AK (Kathmandu University Medical Journal, 2015)
In a first of its kind, a 20 year old Hindu, highlander, working girl presented with abnormal behavior, unrelenting symptoms, had limited benefit by usual treatment and was diagnosed as Possession syndrome. Exorcism offered symptomatic relief. The girl resumed normal activities with no recurrence in a 12 month follow up. Possession syndrome is explained in both medical and theological perspectives. Modern medicine associates it with a mental illness though True Possession syndrome without associated mental illness has been reported. Theological perspective can be amalgamated with current scientific theory and practice, thereby complimenting existing concepts. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12516 Kathmandu Univ Med J 2013; 43(3):253-255